Renal angiomyolipoma with epithelial cysts: a rare entity and review of literature - Wei, Jianguo (Int J Clin Exp Pathol, 2015)
Renal angiomyolipoma (AML) with epithelial cysts (AMLEC) is a comparatively rare benign renal tumor that is recently recognized as a distinct entity and there are relatively few reported cases in the English-language literature. To date 19 cases of AMLEC have been reported in 2 case series and a few case reports. AMLEC has been described as a cystic variant of AML. Herein we reported an AMLEC in a 25-year-old female patient, and to the best of our knowledge this is the first case report of AMLEC in Chinese. She was incidentally found to have a kidney-occupying lesion during a routine medical examination for 1 month. CT examination demonstrated a multilocular cystic lesions arising from right-kidney lower pole. The patient underwent the partial nephrectomy. Histological examination of the tumor was composed of epithelial cysts, compact subepithelial mullerian-like stroma and muscle-predominant AML. Immunohistochemically, epithelial cysts were positive for CK but negative for ER, PR, CD10 and HMB-45; the subepithelial stroma and muscle-predominant AML were positive for ER, PR and HMB-45; the subepithelial stroma was negative for SMA, but muscle-predominant AML was positive for SMA. The final histopathological diagnosis was AMLEC.